Herbal products and food supplements consumption and belief during the COVID-19 pandemic: A study in Java Island, Indonesia - Adi Sutakwa; Pinasthika Rizkia Warapsari Wiratara (Fakultas Pertanian Universitas Ichsan Gorontalo, 2022)
The popularity of herbal products in Indonesia during the COVID-19 pandemic has risen recently. It is believed to be preventive measures to lower the probability of COVID-19 infection and boost immunity. This study explored the knowledge of the Java Island population about COVID-19 and their belief about herbal products and supplements consumption for the prevention of COVID-19 infection. A total of 485 respondents participated in this research. About 84.7% (n = 411) of the participants claimed that they had used herbal products or supplements before the pandemic. Recommendations from friends or relatives (51.1%, n = 248) were the main reason for the respondents to consume herbal products or supplements. Multivitamins (19.6%, n = 95) were the most commonly chosen supplement to increase immunity and reduce the chance of COVID-19 infection. The governments are suggested to provide more evidence-based campaigns to increase population awareness about the use of herbal products and supplements to ensure patient safety.